Peningkatan Aktivitas Value Added Support Function dengan Metode Sampling Kerja di PT. Schneider Electric Manufacturing Batam - Rinaldi Edo Saputro; Tanti Octavia (Jurnal Titra, 2015)
Currently, support function units of PT.SEMB cannot reach their target of performances.Therefore, in this research PT SEMB attempts to evaluate the causes of it. Work samplingmethod is applied for three of support function units. The result shows the proportion ofthe team leader’s, line inspector’s, and line trainer’s value added are 75.04%, 78.16%, and84.19%, respectively. The highest proportion of non value added activities is movement. It occurssince PT.SEMB doesn’t have a working guidance. The proposed improvements are designing achecklist, job rotation procedure, and the guidance for reviewing a job description. The implementationresult shows the proportion of the value added for team leader and line inspector are85.88% and 84.98%